P Wave Dispersion Increases during Hemodialysis Sessions - FAK, ALİ SERDAR; ÖZBEN SADIÇ, BESTE; KOÇ, MEHMET (KARGER, 2009)
Background/Aims: Atrial fibrillation (AF) is common among hemodialysis (HD) patients and is associated with high mortality. P wave dispersion (PWD) is a noninvasive electrocardiographic marker of paroxysmal AF. Our aim was to evaluate the effect of HD session on PWD. Methods: Twenty-five patients (mean age 63 years, 10 males) with sinus rhythm and undergoing chronic HD treatment were included. Blood samples were drawn and 12-lead electrocardiograms were recorded immediately before HD session, at the 2nd hour during HD and at the end of the HD session. The difference between maximum and minimum P wave durations was calculated as PWD. Results: PWD significantly increased during HD sessions compared with predialysis values (41 +/- 12 vs. 21 +/- 10 ms, respectively, p < 0.001), then decreased to a value of 24 +/- 7 ms at the completion of HD, which was not significantly different from the predialysis values. PWD during HD was significantly correlated with predialysis systolic and diastolic blood pressure (r = 0.42, p = 0.037, and r = 0.59, p = 0.002, respectively) and predialysis serum potassium level (r = 0.44, p = 0.031). Linear regression model revealed that predialysis diastolic blood pressure (p = 0.002), predialysis serum potassium level (p = 0.037) and the amount of ultrafiltration (p = 0.048) were the significant predictors of prolonged PWD during HD. Conclusion: PWD increases significantly during HD sessions. This may increase the risk of AF episodes during HD. High diastolic blood pressure and serum potassium level before HD and ultrafiltration amount may predict prolonged PWD during HD. Copyright (C) 2009 S. Karger AG, Basel
Keywords: Atrial fibrillation; Electrocardiography; Hemodialysis; P wave dispersion; SIGNAL-AVERAGED ELECTROCARDIOGRAM; ATRIAL-FIBRILLATION; DURATION; MUSCLE; AGE